Photo‐induced Leishmania DNA degradation by silver‐doped zinc oxide nanoparticle: an in‐vitro approach. Issue 3 (1st June 2016) - Nadhman, Akhtar; Sirajuddin, Muhammad; Nazir, Samina; Yasinzai, Masoom
Abstract : Recently, the authors reported newly synthesised polyethylene glycol (PEG)ylated silver (9%)‐doped zinc oxide nanoparticle (doped semiconductor nanoparticle (DSN)) which has high potency for killing Leishmania tropica by producing reactive oxygen species on exposure to sunlight. The current report is focused on Leishmania DNA interaction and damage caused by the DSN. Here, we showed that the damage to Leishmania DNA was indirect, as the DSN was unable to interact with the DNA in intact Leishmania cell, indicating the incapability of PEGylated DSN to cross the nucleus barrier. The DNA damage was the result of high production of singlet oxygen on exposure to sunlight. The DNA damage was successfully prevented by singlet oxygen scavenger (sodium azide) confirming involvement of the highly energetic singlet oxygen in the DNA degradation process.